Impact of the actions of a nursing program with a promotional approach and self-care in the functional capacity of older adults - Puello Alcocer, Elsy Cecilia; Amador Ahumada, Concepción; Ortega Montes, Jorge Eliecer (Universidad y Salud, 2017)
Introduction: The contributions of health professionals supported by the promotion model allow to demonstrate attitudes, motivations and feelings of the elderly. Objective: To analyze the impact of the actions of a nursing program with a promotional and self-care approach in the strengthening of functional capacity in older adults. Materials and methods: A descriptive-prospective and pre-and post-test intervention without control group in 75 people was carried out with a sampling for convenience. Data collection through survey and Barthel scale was conducted. Results: 48% of the population was in the age range between 67 and 72, 74% were female, 40% were widowed people and 57% were illiterate. An important variation was identified in the modification of the category taking into account the results of the post-test: moderate dependence on mild dependence (71.43%) and mild dependence on independence (30.76%). 82% developed self-care actions, 80% remained active, 78% showed adherence to disease treatment and 90% maintain body hygiene. Conclusions: Continuous nursing actions with a promotional and self-care approach allow reverting limitations in functional conditions of moderate to mild and mild-to-independent dependence, they retain or potentiate the ability to regulate their self-sufficiency and autonomy, thus benefiting the health of older adults.